2021
DOI: 10.3390/ijerph18052401
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Training and Recovery during a Period of Increased Intensity or Volume in Recreational Endurance Athletes

Abstract: The purpose of the study was to examine the effects of progressively increased training intensity or volume on the nocturnal heart rate (HR) and heart rate variability (HRV), countermovement jump, perceived recovery, and heart rate-running speed index (HR-RS index). Another aim was to analyze how observed patterns during the training period in these monitoring variables were associated with the changes in endurance performance. Thirty recreationally trained participants performed a 10-week control period of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Although the individual response magnitudes indicated more positive performance adaptations in HIG, the present statistical findings are in contrast to those of Stöggl and Sperlich 11 and Vesterinen et al, 24 who demonstrated superior performance adaptations of a more polarized intensity distribution with greater HIT load compared to highvolume LIT regimes. However, Ingham et al 25 and Nuuttila et al 26 found similar performance adaptations of high-volume LIT and HIT regimes, which is in line with the present findings and implies that similar performance progression can be achieved both by increased load of LIT and HIT during the preparation period in endurance athletes. In accordance with the hypothesis, increased load of HIT led to 3-4% better VO2max adaptations in running and roller-ski skating compared to increased load of LIT.…”
Section: Discussionsupporting
confidence: 91%
“…Although the individual response magnitudes indicated more positive performance adaptations in HIG, the present statistical findings are in contrast to those of Stöggl and Sperlich 11 and Vesterinen et al, 24 who demonstrated superior performance adaptations of a more polarized intensity distribution with greater HIT load compared to highvolume LIT regimes. However, Ingham et al 25 and Nuuttila et al 26 found similar performance adaptations of high-volume LIT and HIT regimes, which is in line with the present findings and implies that similar performance progression can be achieved both by increased load of LIT and HIT during the preparation period in endurance athletes. In accordance with the hypothesis, increased load of HIT led to 3-4% better VO2max adaptations in running and roller-ski skating compared to increased load of LIT.…”
Section: Discussionsupporting
confidence: 91%
“…Although movement artifacts are not a similar problem in the resting measurements as they might be during exercise, movements during sleep may be a slight issue in restless sleepers. The current PPG recording started 0.5 h after detected sleep onset and continued for 4 h in line with protocols used in previous studies [ 33 , 34 ]. Since the first hours of sleep typically have the highest proportion of slow-wave sleep, representing the most restful and stable period of the night [ 35 ], the 4-h analysis period may speculatively have some benefits compared to the whole night recordings in terms of data quality.…”
Section: Discussionmentioning
confidence: 96%
“…It seems that the parasympathetic hyperactivity may be related to the overreaching/fatigue state itself rather than to the increased training load, as fatigue was not increased at the group level in the current study. The HRV response to the increased training load, an increase or decrease, seems to be individual, despite the type of training ( 25 ). Interestingly, nocturnal HR decreased significantly during the recovery period in the INT group, with no changes at any week in VOL.…”
Section: Discussionmentioning
confidence: 99%
“…The LT1 was set at 0.3 mmol·L −1 above the lowest lactate value and LT2 at the intersection point between 1) a linear model between LT1 and the next lactate point and 2) a linear model for the lactate points measured after the point when La increased at least 0.8 mmol·L −1 for the first time. The same treadmill and lactate threshold estimation protocols have been used in previous studies ( 16 , 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%